Pemanfaatan Ekstrak Kulit Buah Naga Merah (Hylocereus Polyrhizus) sebagai Pewarna Alami dan Antioksidan pada Sediaan Lip Cream - Rahmi, Nur Atikah; Elwina, Elwina; Nahar, Nahar (Politeknik Negeri Lhokseumawe, 2024)
Dragon fruit peel has higher antioxidant activity than dragon fruit peel. Dragon fruit skin can be used as an additional active ingredient in lip cream formulas. This study aims to make cosmetic lip cream from natural ingredients and test its antioxidant activity. Dragon fruit skin extraction was carried out using ethanol as a solvent with the maceration method. Maceration is carried out 3x24 hours. This study used various concentrations of dragon fruit peel extract 3 ml, 5 ml, 7 ml, 9 ml, 11 ml with various carnauba wax concentrations of 0.25 gram, 0.50 gram, 0.75 gram, 1 gram, 1.25 grams. The tests carried out included pH test, irritation test, antioxidant activity test using the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) method, and organoleptic test. The results showed that the best lip cream with a composition of 11 mL dragon fruit peel extract with 0.50 and 0.75 gram carnauba wax had a pH value of 4.7 and 4.8 according to the lip pH standard, namely 4.5-8 SNI 16-4769 -1998, the negative irritation test value for redness, itching and swelling showed that the lip cream preparation did not irritate the lips and the organoleptic test results had an average colour, aroma and texture value of 2.1.